Male graduates transitioning into the workplace: managing stress through the sense of coherence components - Fayard, Kiana; Mayer, Claude-Hélène (Frontiers in Psychology, 2023)
Male graduates are faced with many challenges when transitioning into work life after graduation. This transition from university to the workplace is one of the most important developmental stages in a young adult's life. It has an important impact on their careers and causes increased stress levels. Often, young men are suffering from mental health challenges and feel as though they cannot seek the appropriate help. Thus, it is necessary to determine how young male graduates cope with the changes experienced in this period, especially relating to their sense of coherence and salutogenesis. The aim of the study is to investigate the transition from university to the workplace and to understand their stress and well-being experiences in terms of activating the three sense of coherence components for coping. A qualitative approach is employed through the use of semi-structured interviews with 10 male South African university graduates. A content analysis technique was used to analyse the qualitative data. The findings indicate that most of the young male graduates understand the transition from university to the workplace and the challenges that come with it (comprehensibility). They also have the necessary personal resources to cope with the stress (manageability) while experiencing this life phase as meaningful (meaningfulness). To understand the transition into the workforce was the most important aspect to stay health during the transition. However, male graduates mainly coped by applying their personal coping strategies and mechanisms and thereby managed their transition mainly by themselves, not based on organizational structures or integrative processes. Meaning applied to the transitional process mainly derived from their personal concepts of creating a meaningful life, not as such from the meaning applied to the work or position they held. The findings provide insights which can be used by higher education institutions to prepare graduates for the transition into the workforce and for organizations to develop programmes for graduates to improve their transition into the organization.